2009
DOI: 10.1007/s00534-009-0186-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative recurrence of non‐B non‐C hepatocellular carcinoma

Abstract: Curative resection with adequate surgical margins for single non-B non-C hepatocellular carcinoma can achieve a good outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(50 reference statements)
0
5
0
1
Order By: Relevance
“…However, the literature contains no reports on the prognostic factors for postoperative recurrence and OS in CR-HCC. Given the findings of some previous studies [ 5 , 11 , 15 20 ], we predicted for our study that only the prognostic factors for CR-HCC would be tumor factors and that background liver function would not be prognostic because the liver function of CR-HCC patients is better than that of B-HCC/C-HCC patients. Unexpectedly, however, we found that background liver function was also a prognostic factor for CR-HCC as well as B-HCC/C-HCC.…”
Section: Discussionmentioning
confidence: 96%
“…However, the literature contains no reports on the prognostic factors for postoperative recurrence and OS in CR-HCC. Given the findings of some previous studies [ 5 , 11 , 15 20 ], we predicted for our study that only the prognostic factors for CR-HCC would be tumor factors and that background liver function would not be prognostic because the liver function of CR-HCC patients is better than that of B-HCC/C-HCC patients. Unexpectedly, however, we found that background liver function was also a prognostic factor for CR-HCC as well as B-HCC/C-HCC.…”
Section: Discussionmentioning
confidence: 96%
“…Our research identi ed that the etiology of NBNC-AFP(-)-HCC in patients in China was related to obesity, diabetes, metabolic syndrome, and NAFLD, which is consistent with existing reports [20] . Some factors are associated with the non-alcoholic steatohepatitis (NASH) and liver brosis, such as age, obesity, hypertension, type II diabetes, ALT, S/T >1, and decreased platelet count [21,22] . A series of studies con rmed that obesity and diabetes were independent risk factors for HCC [23] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated that serum Alb is a prognostic factor for OS and serum Alb and AFP for DFS using uni-and multivariate analyses. Until now, reported prognostic factors in patients with NBNC-HCC after hepatic resection include tumor diameter, multiple tumors, portal invasion and curative resection with an adequate surgical margin (13,18), which, however, remain controversial.…”
Section: Discussionmentioning
confidence: 99%